Implications of 3D Forest Stand Reconstruction Methods for Radiative Transfer Modeling: A Case Study in the Temperate Deciduous Forest. Issue 14 (12th July 2022) - Liu, C.; Calders, K.; Meunier, F.; Gastellu‐Etchegorry, J. P.; Nightingale, J.; Disney, M.; Origo, N.; Woodgate, W.; Verbeeck, H.
Abstract: This study investigated the implications of different assumptions of 3D forest stand reconstructions for the accuracy and efficiency of radiative transfer (RT) modeling based on two highly detailed 3D stand representations: 3D‐explicit and voxel‐based. The discrete anisotropic radiative transfer (DART) model was used for RT simulations. The 3D‐explicit and voxel‐based 3D forest scenes were used as structural inputs for the DART model, respectively. Using the 3D‐explicit RT simulation as the benchmark, the accuracy and efficiency of the voxel‐based RT simulation were evaluated under multiple simulation conditions. The results showed that for voxel‐based RT simulations: with voxel sizes 0.1, 1, and 10 m and in blue, green, red, and near‐infrared wavebands, the normalized deviations of simulated directional reflectance exceeded the 5% tolerance limit in 89% viewing directions; with voxel sizes 0.2, 1, and 10 m, the normalized deviations of simulated spectral albedo exceeded the 5% tolerance limit in 90.5% wavelengths; for simulated spectral albedo in blue, green, red, and near‐infrared wavebands and fraction of absorbed photosynthetically active radiation, the normalized deviations exceeded the 5% tolerance limit in 65.3% voxel sizes and spatial resolutions. The two major causes for differences in the 3D‐explicit versus voxel‐based RT simulations were: (a) the difference between light interaction in spatially explicit objects and in turbid medium, and (b) the structural difference of 3D contours between voxel‐based and 3D‐explicit models. However, voxel‐based RT simulations were substantially more computationally efficient than 3D‐explicit RT simulations in large voxel sizes (≥1 m) and coarse spatial resolutions (≥1 m). Key Points: The radiative transfer simulation bias of a voxelized versus spatially explicit canopy exceeds 5% in 81.6% of the simulations Voxelized objects reflected and absorbed less electromagnetic radiation than explicit objects: −45.6% in visible and −6% in NIR bands Voxel sizes 1–2 m are optimal for voxel‐based radiative transfer simulations within the temperate deciduous forest studied